INTEGRASI KECERDASAN BUATAN DALAM PEMBELAJARAN AGAMA HINDU DI ERA DIGITAL - Saputra, Putu Wisnu; I Wayan Rudiarta; Ida Bagus Kade Yoga Pramana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
The digital era presents new challenges and opportunities in the world of education, including Hindu religious education. The integration of artificial intelligence in Hindu religious learning is a strategic step to adapt learning methods to the characteristics of the digital generation. This article examines the potential, implementation and integration of the use of AI in learning Hindu religious education with an analytical-descriptive approach. The findings show that AI is able to enrich the learning process through personalizing materials, increasing interactivity, and expanding learning access. However, the application of AI needs to be accompanied by serious attention to ethical, spiritual and humanistic aspects so that dharmic values ​​are maintained. The role of Hindu religious teachers as spiritual facilitators cannot be replaced, but must work in synergy with technology to produce meaningful learning. Digital infrastructure support, teacher training and ongoing evaluation are key factors in the success of this integration. With a wise and value-based approach, artificial intelligence can become a strategic partner in producing a generation of Hindus who are intelligent, have character and are adaptive to changes and developments over time.